Avaliação da potencialidade do eletrodo compósito à base de grafite/poliuretana modificado com azul da Prússia para determinação de íons k+ em biodiesel - COSTA, Ediani Paurá (2018)
A composite electrode polyurethane graphite (GPU) modified with iron hexacyanoferrate (FeHCF), also known as Prussian Blue (PB), was used for the determination of K + ions in biodiesel samples. The surface of the electrode was coated with PB film by electrodeposition after 50 voltammetric cycles with a scanning speed of 50 mV.s-1 in a potential range of -0.3 to 1.2 V. As electrochemical measurements were performed in solution of potassium phosphate buffer 0.1 mol. L-1 (pH 7.0). The experimental parameters used in the application of the method using the differential pulse voltammetry technique were optimized by obtaining the following conditions: reservoir potential: 0.6 V, pulse amplitude: 50 mV and scanning speed of 5 mV. s-1. The interaction of the analyte with the GPU/PB electrode caused a linear decrease without current signal, which is allowed to extract quantitative values for the potassium concentration in the biodiesel samples of 6.97 x 10-5 ± 1.95 x 10-5 mol. L-1 for the interlaboratory test and 9.29 x 10-5 ± 1.02 x 10-5 mol. L-1 for the laboratory sample. The results were concordant statistically considering the Student's t-test for a confidence level of 95%. The CV values were lower than 25%, and the detection limit was 2.95 x 10-9 and 2.20 x 10-6 mol. L-1 for a certified and laboratory sample, respectively, showing a good accuracy and sensitivity of the proposed method.